The Role of the Glucocorticoids in Developing Resilience to Stress and Addiction - Srinivasan, Subhashini; Shariff, Masroor; Bartlett, Selena (Frontiers in Psychiatry, 2013)
There is emerging evidence that individuals have the capacity to learn to be resilient by developing protective mechanisms that prevent them from the maladaptive effects of stress that can contribute to addiction. The emerging field of the neuroscience of resilience is beginning to uncover the circuits and molecules that protect against stress-related neuropsychiatric diseases, such as addiction. Glucocorticoids (GCs) are important regulators of basal and stress-related homeostasis in all higher organisms and influence a wide array of genes in almost every organ and tissue. Glucocorticoids, therefore, are ideally situated to either promote or prevent adaptation to stress. In this review, we will focus on the role of GCs in the HPA axis and extra-hypothalamic regions in regulating basal and chronic stress responses. GCs interact with a large number of neurotransmitter and neuropeptide systems that are associated with the development of addiction. Additionally, the review will focus on two pathways the orexinergic and cholinergic neurotransmission and highlight their role in stress and addiction. We will provide examples of interactions between GCs and these wherever studied. GCs play a key role in promoting the development of resilience or susceptibility associated with the development of stress-induced addiction and represent important pharmacotherapeutic targets that can reduce the impact of a maladapted stress system for the treatment of stress-induced addiction.